2019
DOI: 10.1101/805010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A survey of spiking activity reveals a functional hierarchy of mouse corticothalamic visual areas

Abstract: 33 The mammalian visual system, from retina to neocortex, has been extensively studied at both 34 anatomical and functional levels. Anatomy indicates the cortico-thalamic system is hierarchical, 35 but characterization of cellular-level functional interactions across multiple levels of this 36 hierarchy is lacking, partially due to the challenge of simultaneously recording activity across 37 numerous regions. Here, we describe a large, open dataset (part of the Allen Brain Observatory) 38 that surveys spiking … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
117
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 76 publications
(129 citation statements)
references
References 92 publications
12
117
0
Order By: Relevance
“…We quantified this variability by the signal-to-noise ratio (SNR) (Figure 1f), and found a mean SNR of 0.11 for the example session, and 0.13 ± 0.01 (s.e.m., n=6) across recordings, similar to the single-trial SNR previously reported for natural image stimuli 38 . We also compared the single-neuron, single-trial signal variance from our two-photon datasets to that from electrophysiological recordings (0.11 vs 0.12) and found that there was little loss of information due to our recording method ( Figure S1a,b) 46 . The aligned, population-averaged tuning curves had a mean half-width at half-max of 14.1 • (Figure S1d ral response vectors for different orientations decayed smoothly as a function of the difference in orientation (Figure S1g,h).…”
Section: Resultsmentioning
confidence: 99%
“…We quantified this variability by the signal-to-noise ratio (SNR) (Figure 1f), and found a mean SNR of 0.11 for the example session, and 0.13 ± 0.01 (s.e.m., n=6) across recordings, similar to the single-trial SNR previously reported for natural image stimuli 38 . We also compared the single-neuron, single-trial signal variance from our two-photon datasets to that from electrophysiological recordings (0.11 vs 0.12) and found that there was little loss of information due to our recording method ( Figure S1a,b) 46 . The aligned, population-averaged tuning curves had a mean half-width at half-max of 14.1 • (Figure S1d ral response vectors for different orientations decayed smoothly as a function of the difference in orientation (Figure S1g,h).…”
Section: Resultsmentioning
confidence: 99%
“…Superior colliculus receptive fields in rat have been reported with diameters ranging from 10° to 60°. Larger receptive field sizes in LP neurons have also been reported in mice (Allen et al, 2016;Bennett et al, 2019;Siegle et al, 2019).…”
Section: Single Cell Response Characteristics In Rat Pulvinarmentioning
confidence: 64%
“…3F, 3G, and S3 respectively). For reference, data from in vivo extracellular Neuropixels recordings from awake mice within a standard pipeline (Siegle et al, 2019) are included in Fig. 3F (data available by the Allen Institute, brain-map.org/explore/circuits/visual-coding-neuropixels) and are used throughout the manuscript as a benchmark (examples in Fig.…”
Section: Creating and Testing Thalamocortical Connectivitymentioning
confidence: 99%
“…The latter variant can be run on a single CPU, making it broadly accessible to all neuroscientists. Both variants are constrained by experimental measurements and reproduce multiple observations from in-house Neuropixels high-density electrical recordings in vivo (Siegle et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation